This is how it was - Pagliari, Nicole, author; Altschul, Andrew, advisor; Ausubel, Ramona, committee member; Chatterjee, Sushmita, committee member (Colorado State University. Libraries, 2024)
This Master's thesis is a collection of short stories that interrogate instances of racial aggression against Filipino and Filipino-American women alongside the existential dread of being a young woman and regret and robots in varying quantities and combinations. These stories all share a common goal of analyzing poignant moments of reckoning for their female protagonists of varying physical presentations, socio-economic statuses, and stages of life while also experimenting with speculative elements and voice.